2015 IMC (New York, 2015)
Designed to provide comprehensive regulations for mechanical systems and equipment, it includes coverage of HVAC, exhaust systems, chimneys and vents, ducts, appliances, boilers, water heaters, refrigerators, hydronic piping, and solar systems. This valuable reference uses prescriptive- and performance- related provisions to establish minimum regulations for a variety of systems. This updated code includes information on condensate pumps, and the ventilation system for enclosed parking garages.
Keywords: Vật lí ứng dụng,Mechanics, applied